Lasting Effects of an Import Shock: Channels of Adjustment - Polina Knutsson (Lund University, School of Economics and Management, Department of Economics, 2020)
This paper exploits a quasi-natural experiment to study the channels of labor market adjustment to an import shock. Using matched employer-employee data from Sweden, I study workers' adjustment after the removal of quotas set out by the Multi-Fiber Arrangement for Chinese producers upon China's entry into the WTO. I find evidence of substantial losses in terms of earnings and employment. Sectoral mobility mitigates a portion of these losses, but gives rise to substantial adjustment frictions. The largest losses accrue to workers with skills specific to the exposed industry. Some losses are recovered through mobility across labor markets, but only workers in high-skill occupations benefit from this channel. I also show that skill specificity of the local labor market is an important determinant of adjustment and provide evidence of skill upgrading in response to the import shock.
Keywords: F14; F16; J24; J31; 330; Import competition; worker mobility; human capital